As estratégias de sobrevivência das populações ribeirinhas em João Pessoa-PB: o caso da comunidade Mangue-Seco no bairro da Ilha do Bispo. - Santos, Hamilton da Silva (2006)
The present study has the objective to localize and analyse some aspects of life s quality from poor population, especially the ribeirinhas, focalizing in the strategy of survival that this populations develop to assure their sustenance. Our object of research is the ribeirinha Mangue-Seco community localized in the section named Ilha do Bispo, that represent this spectacle of peculiar poverity in urban environment from peripheric world, consequence of accelerate and disarranged urban progress, that provoke socials and surroundings troubles. Therefore, according many social problems from this and others communities is necessary an amplification of theoric debate and effective actions to culminate viabilities propositions to solution, or attenuation of this problems to that we might life in environment more equanimi.